PENETAPAN KADAR PROTEIN DALAM SUSU FORMULA BAYI DAN ASI DI MEDAN SECARA KJELDAHL - Eka Margaret Sinaga; Siti Maimunah; Erly Sitompul (Jurnal Farmanesia, 2019)
Breast milk (ASI) is the best food for babies. Breast milk has advantages compared to other milk, including guaranteed cleanliness, the composition of breast milk is also very suitable for digestion, growth, and development of babies, one of the compositions contained in breast milk is protein. Currently, many mothers cannot breastfeed their own babies, so they choose infant formula as a substitute for breast milk. The purpose of this study was to determine differences in protein levels in infant formula and breast milk. Determination of protein content was carried out using the Kjeldahl method which is a simple method for determining total nitrogen in protein and other nitrogen-containing compounds. The Kjeldahl method is carried out through 3 processes, namely: the destruction process, the distillation process, and the titration process according to the procedures and tools used in the Chemistry Laboratory of the Sari Mutiara Indonesia University. The results of the determination of protein levels using the Kjeldahl method contained a protein with average levels in infant formula brand A (10.10 ± 0.96) %, infant formula brand B (10.95 ± 2.43) %, infant formula brand C (11.0666 ± 1.6932) %, and breast milk (20.5733 ± 3.1828) %.